ANALISIS KOMPARATIF RISIKO HARGA KOMODITI BAWANG MERAH DAN BAWANG PUTIH DI SULAWESI SELATAN - Tanty Azisah; Mohammad Natsir; Nurdin Mappa; Ratnawati Tahir; Sri Mardiyati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Risk is defined as the probability of an expected event occurring. An increase in the probability of a small profit will increase the risk of a business. Price fluctuations are a common occurrence in the marketing of shallots and garlic commodities. This study aims to analyze the price risks of shallots and garlic and compare them in South Sulawesi Province. This research is quantitative, with time series data on shallot and garlic prices in South Sulawesi Province from 2021 to 2025 sourced from the Central Statistics Agency (BPS) of Makassar City, South Sulawesi, the South Sulawesi Provincial Food Security Office, the Strategic Food Price Information Center, and other sources. The research data was collected using literature study techniques. Data analysis techniques include Variance Calculation, Standard Deviation, and Coefficient of Variation to analyze price risk, and a t-test to compare the risk levels of shallot and garlic prices. The results showed that the average price of garlic in South Sulawesi (Rp 29,345.69/kg) was higher than that of shallots (Rp 27,933.33/kg) during the 2021-2025 period. Although both commodities have high price volatility and fluctuations (standard deviation of 7.675), shallots pose a higher risk due to their higher coefficient of variation (75.85%) compared to garlic (63.92%). The t-test results revealed a significant difference between the average prices of shallots and garlic in South Sulawesi Province for the period 2021 to 2025. This was concluded because the significance value of 0.025 < 0.05 and the calculated t-value (2.2427) > t-table (1.9646).